Analysis of Gayo Poet Traditional Communication Media In Building Community Islamic Insights Central Aceh District - Abdullah, Yusnadi, Salman Yoga S (LPPPIPublishing, 2021)
This study aims to determine the Analysis of Gayo Poet Traditional Communication Media In Building Community Islamic Insights Central Aceh District by using qualitative research methods using data collection techniques such as Observation, Documentary, and Interview. The data that has been collected, compiled systematically, then read, translated, understood, and classified based on the coding that has been determined. Furthermore, explore and analyze the data carefully and take into account other appropriate references. The results of the research are that the